The Impact of Social Capital on Sustainable Development of Agriculture in Rural Areas (Case Study: Kermanshah Province Villages) - Vakil Haidari Sareban; Sohyla Bakhtar; Mina Ziarati (جغرافیا و پایداری محیط)
The agriculture part is one of the main sources of employment providing income whose sustainability causes the rural economics and environmental sustainable within the agricultural systems and rural communities. Social capital is one of the factors that have effect on it, because achieving sustainable development is not possible without partnership, trust and solidarity. So this research is done to evaluate the impact of social capital on sustainable development of agriculture in rural areas. The statistical society is Kermanshah province villages those 84 villages and 441 people were selected as samples. Field methods were used to collect data. Moreover, a framework of six indicators of social capital (trust, consistency, and consistency) and sustainable agriculture (social, economic and environmental) in the form of 63 items were selected in order to analyze the subject. Validity of the questionnaire was proved by the experts and required changes were done. Its reliability was calculated by using Cronbach's alpha and its total reliability was 0.815. The results of research findings indicate that there is a positive and significant relationship between social capital and sustainable development of agriculture. Besides, the results of multivariate regression showed that the components of social capital explain 685% of the changes in agricultural sustainable development. Based on the results of single-sample T test, we can say the indicators of agricultural sustainable development are at an undesirable level. Thus, the existence of social capital in rural areas plays a key role in rural development, because rural development is created by participation, trust and local cohesion leading to increase the level of knowledge and awareness of farmers in the field of correct management of Farms and their skills. Extended Abstract 1-Introduction Through the emphasis on trustworthy, cooperation , participation, coherence and activity in local networks Farmers' social capital, social capital is considered as a major factor, and its level can affect the type of sustainable agricultural policies, rural economic diversification and more appropriate productivity of production inputs. Kermanshah Province with about 25% of rural population and a wide and diverse geographical territory, with most villages is located in mountainous area, necessitates for establishment and achievement sustainable agricultural development. Initially, the status of the region and the views of the villagers in this area and the factors that affect sustainable agriculture should be investigated. Therefore, this study has been carried out in order to examine the effects of social capital on sustainable development of agriculture in rural areas of Kermanshah province. The aim of this paper is to achieve the goals such as studying the relationship between social capital and sustainable development of agriculture, investigating the effects of social capital indicators on sustainable development of agriculture and surveying the status of indicators of sustainable agricultural development. 2-Materials and Methods Regarding the aim of the study, this is an applied one, but methodologically, this research has descriptive-analytical nature. The statistical population of the study is 478,444 rural residents that settle in 85 rural districts of Kermanshah province. In this research, using the Cochran formula, the sample size was 385, which promoted to 441 in order to achieve better results. Multi-stage stratified random was used to sampling, so that, among the rural districts of each township 2 rural districts and from each rural districts 3 villages and among them 5 villagers were selected as the sample. Finally, 84 villages were selected to distribute the questionnaire in 14 township of the province. Sampling method in each village is randomly systematic. To conduct research, three social capital indicators (trust, consistency, and consistency) in the form of 29 items were used and three main indicators of sustainable agriculture (social, economic and environmental) were used in the form of 34 items. The required data were collected by using documentary study and field studies (questionnaire and interview). The questionnaire was basically designed with closed questions in the form of the Likert Five Spectrum Option. Validity of the questionnaire was proved by the experts and required changes were done. Its reliability was calculated by using Cronbach's alpha and its total reliability was 0.815. Descriptive statistics and inferential statistics were used to analyze the data. In the descriptive statistics section, the mean and standard deviation were used and in the inferential statistics, Pearson correlation test (to examine the relationship between variables), regression test (to examine the effect of independent variable in dependent variable), and one-sample t-test (to measure the villagers' viewpoints about variables Research) were used. 3-Results and Discussion Distributed questionnaires were filled by 420 respondents in studied villages. (51.66) of respondents were men and (48.44) were women. In terms of the level of education from among the 4 educational levels, about 32% of respondents with the highest frequency were graduate students. Regarding the marital status of respondents, 286 were married and 134 were single. The results of Pearson correlation coefficient to examine the correlation between social capital and sustainable agriculture showed that there is a positive and significant relationship between the components of research and the components of social participation with a correlation coefficient of 0.764 and a significance value of 0.303. 0 has the highest correlation with sustainable agriculture. The results of multiple regression coefficient indicate that according to the significance level of the test for the confidence level of 0.95, among the social capital indices, the social trust index has the highest effect on the dependent variable with the beta coefficient of 0.653 and can explain the 685/0 of the variance of sustainable agriculture. The results of this study indicate that, among three factors of social capital, the most important factor in the agricultural sustainability is social trust. According to the average of the three main sustainability indicators that was estimated 2.82; sustainable agriculture in the studied villages is in the Undesirable level. On the other hand, it can be concluded that there is a correlation between farmers' social capital and sustainable development of agriculture and by promoting the level of participation, social trust and social cohesion of farmers, their attitude towards sustainable agriculture will improve. As a matter of fact, the requirement for sustainable agricultural development is improving. According to the results, the correlation coefficient between the two independent and dependent variables was 0.77, which show a direct and positive correlation. 4-Conclusion It can be argued that the existence of social capital in rural areas plays a key role in rural development, because rural development is created by participation, trust and local cohesion increasing the level of knowledge and awareness of farmers in the field of correct management of farms and their skills. On the other hand, by reducing poverty and increasing income, the production and investment in agricultural affairs prevent the farmers from emigration from rural areas, for the stability of price of agricultural yields, reducing the supply and demand for them and balancing the land incentives to encourage farmers to diverse cultivation lead to economic sustainability. Finally, due to the analysis of the results and with the aim of developing sustainable agriculture, the suggestions such as increasing the number of meetings and holding meetings among farmers, development and improvement of intra-group relations and group-based management for shared resource can help its development leading to sustainable agriculture.